PRIVATE ACTOR RIGHTS DERIVED FROM THE WTO TFA - Ozy Diva Ersya (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2019)
The lack of a legal protection for private actors at the domestic level surely brings disadvantages for them as they are not likely to have any legal foundation to enforce their rights when domestic law violates WTO law. State actions or trade measures in national or international trade directly affect private actors in terms of the sustainability of their economic activity at the domestic level. In addition, the purpose of the WTO of establishing global free markets is a threat to the practices of protectionist countries and clashes with the idea of a territorial border of a state. The paper examines the uniqueness of the WTO TFA in the implementation of its provisions and it argues that the WTO TFA envisages provisioned rights for private actors. However, the invocation of these rights in the WTO TFA for the interest of private actors is only possible by the power of domestic court of a state Abstrak: Kurangnya perlindungan hukum atas hak-hak pengusaha dalam melakukan bisnis lintas negara di tingkat hukum nasional memberikan kerugiaan bagi mereka ketika tidak tersedianya payung hukum untuk menegakan secara hukum hak-hak mereka saat aturan nasional bertentangan dengan aturan WTO. Kebijakan perdagangan suatu negara atau internasional tentunya sangat berpengaruh atas kelangsungan bisnis mereka didalam negeri. Selain itu, tujuan WTO untuk menciptakan perdagangan bebas dunia adalah suatu ancaman bagi negara-negara yang memproteksi perdagangannya dan tujuan WTO sendiri juga bertentangan dengan batas-batas wilayah antar negara. Kajian ini menganalisa keunikan WTO TFA dalam mengimplementasikan pasal-pasalnya dalam hukum nasional negara-negara anggota WTO dan berpendapat bahwa WTO TFA memberikan perlindungan hak-hak kepada pengusaha. Akan tetapi, penegakan hak-hak tersebut akan sangat tergantung pada wewenang hakim pengadilan suatu negara. Kata Kunci: Hak Aktor Pribadi, Organisasi Perdagangan Dunia (WTO), PerjanjianFasilitasi Perdagangan (TFA)